Corporate Social Responsibility (CSR) Disclosure Behavior in the Global Business Sector - Nandyta Frismaya Putri; Armiani Armiani (International Journal of Economics, Management and Accounting, 2025)
This research explores the impact of sustainable accounting policies on the disclosure behavior of Corporate Social Responsibility (CSR) in the global business sector. As companies increasingly recognize the importance of integrating sustainability into their business strategies, CSR disclosure has become a critical aspect of maintaining stakeholder relationships. Sustainable accounting policies play a key role in ensuring that CSR activities are transparently reported in financial statements. This study adopts a literature review methodology to examine previous research on the influence of sustainable accounting practices on CSR disclosure. The findings indicate that companies with clear and structured sustainable accounting policies tend to provide more transparent and comprehensive CSR disclosures. Furthermore, the adoption of international standards, such as GRI and SASB, significantly enhances the quality and consistency of CSR reporting. The study concludes that the implementation of effective sustainable accounting policies improves the transparency and trustworthiness of CSR disclosures, which can positively impact a company's reputation and stakeholder relations.